Ancestry informative markers: A foundation for unravelling genetic ancestry and population structures - Akanksha Chaudhary,; Nidhishree N.S,; Rakesh Kumar Pundir,; Amod Kumar, (Journal of Livestock Biodiversity, 2025)
Deciphering the genetic ancestry in livestock species has important applications in population stratification andis to used explore the genetic basis for differences among the breeds within the populations. Genetic ancestryplays a crucial role in identifying population structure by determining the number of subpopulations within apopulation and assigning individuals to their respective groups. It is also instrumental in defining the numberof ancestral populations in admixed populations and estimating the proportions of these ancestral populationsin admixed individuals. The study of Ancestry Informative Markers (AIMs) has significantly advanced ourunderstanding of genetic variation within populations, with applications ranging from anthropology to livestockmanagement. AIMs are specific genetic markers, such as SNPs, that show significant allele frequency differencesbetween populations, allowing researchers to trace lineage and analyse population structure. With the advent ofnext-generation sequencing technologies and SNP genotyping, AIMs have become invaluable for uncovering thebiogeographical origins of species, aiding in conservation efforts, and improving livestock breeding strategies. Inthis review, we have briefly explained an overview of about the AIMs, methods of estimation and their importancein livestock management.